EFFECTIVENESS OF LATERAL WEDGE INSOLE ON KNEE OSTEOARTHRITIS OUTCOMES IN PAKISTANI POPULATION - Rabbiya Riaz; Omar W Althomali; Bushra Sultana; Imran Amjad; Sammar Abbas; Nasir Khan (The Rehabilitation Journal, 2022)
Background: Osteoarthritis (OA) is a persistent joint disorder, which normally affects the weight bearing joints especially knee joint. Lateral wedge insole is one such approach suggested by professionals to manage the knee osteoarthritis. Objective: To determine the effectiveness of lateral wedge insoles on knee osteoarthritis outcomes in Pakistani population Design: A single-blinded, pretest-posttest comparison. Setting: District Headquarter (DHQ) Hospital, Bahawalnagar and National Institute of Rehabilitation Medicine (NIRM), for a time period of one month. Population: Patients with the age criteria of 40-70 years, and who had knee OA were included in the study. Methods: Participants were randomly divided in two groups; lateral wedge insoles (LWI) group (n=20), and conventional physical therapy (CPT) group (n=20). Pain, stiffness, activities of daily living, sports and recreational activities, and quality of life was assessed on Urdu version of Knee Injury and Osteoarthritis Outcome Score scale (KOOS) on every week till 4th week of intervention. Mixed ANOVA was used for interaction effect of between-subject factor (group) and within-subject factor (time) with-in group analysis and one way ANOVA for between group comparisons with their effect size (ɳp2). Results: Significant improvement with large effect size was observed in Symptoms and stiffness (p<0.001, ɳp2=.329} , pain (p<0.001, ɳp2=.559), functional activities (p<0.001, ɳp2=.394), recreational activities (p<0.001, ɳp2=.369) and quality of life (p<0.001, ɳp2=.280). The CPT group showed more significant improvement (p<0.001) in all domains of KOOS as compared to LWI group. Conclusion: Lateral wedge insoles (LWI) and conventional physical therapy (CPT) both have positive impact on knee osteoarthritis outcomes. But conventional physical therapy was more effective in improving functional independence. Clinical rehabilitation impact: This study provides the evidence on the use of LWI and CPT as alternative strategies to improving Knee OA outcome measures. Keywords: Knee osteoarthritis, functional independence, geriatric population, musculoskeletal physiotherapy, orthotics, quality of life, rehabilitation